Phonological Studies of Arabic based on Classical and Contemporary Scholars | الدرس الفونولوجي العربي بين القديم والحديث - Saepul Anwar (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
This paper describes how phonological studies are carried out in the era of classical scholars and contemporary scholars. Among the findings of this paper, the difference between phonological studies between classical scholars and contemporary scholars is in the approach they take. if classical scholars only provide their studies with simple observations using the five senses, then contemporary scholars use technological advances by utilizing laboratories that exist for the accuracy of their descriptions for the sound nature of language. it is not surprising if the findings of contemporary scholars of phonology are more detailed than the findings of classical scholars of phonology.